Trust - "Gibb, Jack R" (Los Angeles, 1978)
This book is my personal statement of my beliefs and attitudes about trust, which is the primary construct of TORI (Trust Level ) theory. It is also a description of the theory, meant for the general reader interested in trust and its singular relevance to today's world. It is addressed to all parents, managers, teachers, therapists, ministers- to any person who is interested in becoming more role-free, which is at Lorraine Gibb and I are creating our lives and TORI theory together, and thus in a very real sense we are co-authoring this book out of our shared years of living.
Keywords: Trust (Psychology)